Stroke-Induced Central Pain: Overview of the Mechanisms, Management, and Emerging Targets of Central Post-Stroke Pain - Anugeetha Thacheril Mohanan; Sermugapandian Nithya; Yousra Nomier; Dalin A. Hassan; Abdulmajeed M. Jali; Marwa Qadri; Shamna Machanchery (MDPI AG, 2023)
The incidence of stroke plays the foremost role in the genesis of central neuropathic pain. Central post-stroke pain (CPSP) is a central pain arising from a vascular lesion in the central nervous system that elicits somatosensory deficits, often contralateral to stroke lesions. It is expressed as continuous or intermittent pain accompanied by sensory abnormalities like dysesthesia and allodynia. CPSP remains de-emphasized due to the variation in onset and diversity in symptoms, besides the difficulty of distinguishing it from other post-stroke pains, often referred to as a diagnosis of exclusion. Spinothalamic dysfunction, disinhibition of the medial thalamus, and neuronal hyperexcitability combined with deafferentation in thalamocortical regions are the mechanisms underlying central pain, which play a significant role in the pathogenesis of CPSP. The treatment regimen for CPSP seems to be perplexed in nature; however, based on available studies, amitriptyline and lamotrigine are denoted as first-line medications and non-pharmacological choices may be accounted for cases intractable to pharmacotherapy. This review attempts to provide an overview of the mechanisms, existing management approaches, and emerging targets of CPSP. A profound understanding of CPSP aids in optimizing the quality of life among stroke sufferers and facilitates further research to develop newer therapeutic agents for managing CPSP.